Pharmacokinetics of oral doxycycline during combination treatment of severe falciparum malaria. - Newton, P; Chaulet, J; Brockman, A; Chierakul, W; Dondorp, A; Ruangveerayuth, R; Looareesuwan, S; Mounier, C; White, N (2005)
The pharmacokinetics of oral doxycycline administered at 200 mg every 24 h were investigated in 17 patients recovering from severe Plasmodium falciparum malaria. The data suggest that the doses of doxycycline currently recommended (circa 3.5 mg/kg of body weight daily) may not be optimal.